2018
DOI: 10.1021/acs.est.8b00020
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Potential for Agricultural Benefits from Pollinator Habitat at Solar Facilities in the United States

Abstract: Of the many roles insects serve for ecosystem function, pollination is possibly the most important service directly linked to human well-being. However, land use changes have contributed to the decline of pollinators and their habitats. In agricultural landscapes that also support renewable energy developments such as utility-scale solar energy [USSE] facilities, opportunities may exist to conserve insect pollinators and locally restore their ecosystem services through the implementation of vegetation manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 36 publications
0
48
0
Order By: Relevance
“…For example, in the UK, active management for wildlife across 11 solar energy power plants (on predominantly former grazing land), increased diversity and abundance of broad-leaved plants, grasses, invertebrates, and birds, compared to control plots 31 . A recent study in the US identified 3,500 km 2 of agricultural land near existing and planned ground-mounted solar energy power plants that could benefit from nearby indigenous pollinator habitat 32 . Lastly, restoration actions may confer a positive feedback to PV module efficiency.…”
Section: Optimizing Land Resources For Tess Of Solar Energymentioning
confidence: 99%
“…For example, in the UK, active management for wildlife across 11 solar energy power plants (on predominantly former grazing land), increased diversity and abundance of broad-leaved plants, grasses, invertebrates, and birds, compared to control plots 31 . A recent study in the US identified 3,500 km 2 of agricultural land near existing and planned ground-mounted solar energy power plants that could benefit from nearby indigenous pollinator habitat 32 . Lastly, restoration actions may confer a positive feedback to PV module efficiency.…”
Section: Optimizing Land Resources For Tess Of Solar Energymentioning
confidence: 99%
“…A new estimate of average annual per MW bird mortality for southern California was calculated using the PV solar (only) dataset presented in our study. In addition, we also extrapolated avian fatalities to all of California and Nevada, using updated solar buildout statistics from Walston et al [8].…”
Section: Comparison Of Fatality Estimates With Other Studiesmentioning
confidence: 99%
“…Including the estimate from CC1-2 raises the average fatality rate to 2.49 birds/MW/year, or 14,940 bird fatalities/ year in Southern California. We also took updated estimates of USSE development in California (14.562 GW) and Nevada (2.458 GW) from Walston et al [8] to derive an updated range of known and unknown cause estimates for all of California and Nevada: 30,976 (excluding CC1-2) to 42,193 (including CC1-2) bird fatalities per year.…”
Section: Comparison Of Fatality Estimates With Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, land sparing can also be achieved with an intensification of energy generation that increases its land use efficiency [36,37]. The use of water bodies as a recipient environment for solar energy infrastructure may be particularly attractive considering its potential for land sparing [2].…”
Section: Introductionmentioning
confidence: 99%